PENDAMPINGAN KAPASITAS SUMBER DAYA MANUSIA YANG MENGEDEPANKAN BUDAYA DAN KEARIFAN LOKAL PADA BADAN USAHA MILIK DESA ADAT SUWAT KABUPATEN GIANYAR - Gde Bayu Putra, Cokorda; Putra Astawa, I Putu; Putu Widani Sugianingrat, Ida Ayu; Astrama, I Made; Yudy Wijaya, Putu; Ayu Lestari Wijayanti, Ni Ketut (Universitas Hindu Indonesia, 2025)
Capacity Building for Human Resources Prioritizing Culture and Local Wisdom in the Village-Owned Enterprise of Suwat Traditional Village, Gianyar Regency is an effort to enhance the capacity of the management of Suwat Waterfall tourist attraction by emphasizing the understanding of Bali's cultural values and local wisdom. Suwat Traditional Village, with its natural tourism potential, faces challenges in managing human resources, the majority of whom come from an agrarian community with limited educational backgrounds. Therefore, it is necessary to provide guidance that focuses on strengthening competencies in tourism service based on local ethics, culture, and religiosity. The assistance is carried out through the development of educational materials that integrate Bali's cultural values and direct training to improve the skills of managers and staff in managing services and the organization. The outcomes of this activity are expected to strengthen the competitiveness of Suwat Waterfall as a cultural tourist destination, foster solidarity among the management team, and uphold local wisdom in every aspect of its operations. Through this education, it is hoped that the managers of Suwat Waterfall will be able to run the business with a more professional, culturally-aware attitude, and in accordance with traditional values that are the foundation for the sustainability of the business and environmental preservation.